Students’ perception of attributes of independent colleges of business profile in the market of higher education in Poland - Dejnaka Agnieszka; Kulig-Moskwa Katarzyna; Łobos Krzysztof; Nogieć Joanna; Szewczyk Mirosława (Management)
The article examines the general attributes which are in use by clients (students) in the process of evaluation of non-public colleges of business profile in Poland. The evaluations are presented in comparison with other academic institutions having the same profile, both independent and public ones. In the research part, the method of factor analysis was used with the aim of distinguishing the general values which are in students’ use. The most important conclusion resulting from the work is that students of non-public colleges perceive two basic types of attributes regarding a business school, that is practical and academic assets, yet they are most clearly governed by a more pragmatic than academic system of values and choose colleges which – beyond any doubt – offer the model of vocational teaching supported by practice.